Dzieło literackie w perspektywie metodologii międzydyscyplinarnej a dydaktyka literatury = Literary Work in the Perspektive of Interdisciplinary Methodology (and Didactics of Literature) - Ludorowski, Lech (Zielona Góra: Lubuskie Towarzystwo Naukowe)
At first the author defines the principle research thesises of the dissertation`s problems and the concept of interdisciplinary methodology. He adopts the view, that a literary work can and should be examined not only in its "natural" aesthetical context but also in connection with other provinces of fine arts science. Especially the field of music and music theory seems to be of great help. This is proved by the near relationship between the fine art of word and the fine art of sound within common forms (for instance song or libretto) and common kinds of modern art (play or screen play) as well as the affinity to related fields of science.
Keywords: dydaktyka literatury; dzieło literackie; metodologia